Chemotherapy in Combination With Radiotherapy for Definitive-Intent Treatment of Stage II-IVA Nasopharyngeal Carcinoma: CSCO and ASCO Guideline. Issue 7 (1st March 2021) - Chen, Yu-Pei; Ismaila, Nofisat; Chua, Melvin L. K.; Colevas, A. Dimitrios; Haddad, Robert; Huang, Shao Hui; Wee, Joseph T. S.; Whitley, Alexander C.; Yi, Jun-Lin; Yom, Sue S.; Chan, Anthony T. C.; Hu, Chao-Su; et al.
Abstract : PURPOSE: The aim of this joint guideline is to provide evidence-based recommendations to practicing physicians and other healthcare providers on definitive-intent chemoradiotherapy for patients with stage II-IVA nasopharyngeal carcinoma (NPC). METHODS: The Chinese Society of Clinical Oncology (CSCO) and ASCO convened an expert panel of radiation oncology, medical oncology, surgery, and advocacy representatives. The literature search included systematic reviews, meta-analyses, and randomized controlled trials published from 1990 through 2020. Outcomes of interest included survival, distant and locoregional disease control, and quality of life. Expert panel members used this evidence and informal consensus to develop evidence-based guideline recommendations. RESULTS: The literature search identified 108 relevant studies to inform the evidence base for this guideline. Five overarching clinical questions were addressed, which included subquestions on radiotherapy (RT), chemotherapy sequence, and concurrent, induction, and adjuvant chemotherapy options. RECOMMENDATIONS: Evidence-based recommendations were developed to address aspects of care related to chemotherapy in combination with RT for the definitive-intent treatment of stage II to IVA NPC. Additional information is available at www.asco.org/head-neck-cancer-guidelines .